Investigation on non-uniform temperature distribution in a solar cell with associated laser beam heating. (1st January 2021) - Zhai, Han; Zhang, Jia; Wu, Zihua; Xie, Huaqing; Li, Qiang
Highlights: Investigations on the non-uniform temperature rise have been conducted. Temperature deterioration effect has been observed. Ranges of deterioration under various conditions were obtained. Mechanisms of temperature deterioration have been proposed. Non-uniform temperature distribution would become worse under working condition. Abstract: Temperature rise of a solar cell under various non-uniform working conditions has been investigated. An infrared laser beam irradiating the front surface of the solar cell was used to provide different non-uniform temperature distributions by altering its output energy. Variation of the temperature distribution has been analyzed by numerical simulation and experimental measurements when the solar cell was exposed to sunlight with different intensities of 2280, 2150, 1000, and 750 W/m 2, respectively. The results showed that the region of solar cell with higher initial temperature could absorb more heat energy and obtain higher final temperature than that with lower initial temperature after exposure to a same sunlight. The difference of temperature rise between higher and lower temperature regions is proportional to the initial temperature difference approximately. The ratios of temperature rise difference to initial temperature difference were about 24.8%, 20.0%, 14.2% and 10.0%, respectively, under the different sunlight intensities of 2280, 2150, 1000, and 750 W/m 2 . A deterioration effect has been observed that the degree of non-uniform distribution in solar cell would be enhanced when solar cell working in high sunlight intensity, resulting in the attenuation of the photovoltaic performance.